2018
DOI: 10.3892/or.2018.6952
|View full text |Cite
|
Sign up to set email alerts
|

SHCBP1 is a novel target and exhibits tumor‑promoting effects in gastric cancer

Abstract: The present study investigated the expression and potential influence of SHC SH2 domain-binding protein 1 (SHCBP1) in gastric cancer (GC) cells. SHCBP1 is closely related to cell proliferation and cell cycle progression, but its role in GC remains unclear. The TCGA database revealed that SHCBP1 is highly expressed in GC tissues. Furthermore, SHCBP1 was revealed to be highly expressed in GC cell lines MGC-803 and SGC-7901 cells, and downregulation of SHCBP1 significantly inhibited GC cell proliferation. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Based on the bioinformatics analysis of a large number of glioma specimens, we found that PART1 and hsa-miRNA-429 could regulate SHCBP1 expression and that SHCBP1 can be used as a molecular biomarker to judge the prognosis of glioma patients. Previous studies have found that SHCBP1 acts as a cancer-promoting gene in a variety of tumors [19][20][21][22][23], which is consistent with our findings. We also discovered multiple tumor-associated signaling pathways, such as cell cycle and DNA replication, that may lead to glioma development.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on the bioinformatics analysis of a large number of glioma specimens, we found that PART1 and hsa-miRNA-429 could regulate SHCBP1 expression and that SHCBP1 can be used as a molecular biomarker to judge the prognosis of glioma patients. Previous studies have found that SHCBP1 acts as a cancer-promoting gene in a variety of tumors [19][20][21][22][23], which is consistent with our findings. We also discovered multiple tumor-associated signaling pathways, such as cell cycle and DNA replication, that may lead to glioma development.…”
Section: Discussionsupporting
confidence: 93%
“…hsa-miRNA-429 plays an inhibitory role in a number of tumors [39][40][41], including glioma [42][43][44]. SHCBP1 is involved in the development of hepatocellular carcinoma [21], glioma [19], breast cancer [22], and gastric cancer [23]. However, the lncRNAs and miRNAs with which SHCBP1 interacts and whether it could be used as a prognostic molecular biomarker had been unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SHCBP1 expression was higher in breast cancer compared with adjusted tissue and it correlated with worse cancer stage and poor survival [72]. SHCBP1 was shown to promote gastric cancer [73]. SHCBP1 is upregulated in lung cancer cell lines and plays a role in apoptosis [74].…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, SHCBP1 suppressed apoptotic and promoted cell cycle progression which accelerated tumor growth and invasiveness. 31 .…”
Section: Overexpression Of Bub1b Cdk1 Ccna2mentioning
confidence: 99%